A quantitative approach for measuring the degree of flexibility of business process models - Mejri, Asma (2018)
Purpose The purpose of this paper is to measure the flexibility of business process models. The authors give the notions of flexible process distance, which corresponds to the number of change operations needed for transforming one process model into another, considering the different perspectives (functional, operational, behavioral, informational, and organizational). Design/methodology/approach The proposed approach is a quantitative-based approach to measure the flexibility of business process models. In this context, the authors presented a method to compute the distance between two process models. The authors measured the distance between a process model and a process variant in terms of the number of high-level change operations (e.g. to insert or delete actors) needed to transform the process model into the respective variant when a change occurred, considering the different perspectives and the flexible features. Findings To evaluate the flexibility-measurement approach, the authors performed a comprehensive simulation using an emergency care (EC) business process model and its variants. The authors used a real-world EC process and illustrated the possible changes faced in the emergency department (possible variants). Simulation results were promising because they fit the flexibility needs of the EC process users. This was validated using the authors’ previous work which consists in a guidance approach for business process flexibility. Research limitations/implications The authors defined six different distances between business process models, which are summarized in the definition of total process distance. However, changes in one perspective may lead to changes in other perspectives. For instance, adding a new activity may lead to adding a new actor. Practical implications The results of this study would help companies to obtain important information about their processes and to compare the desired level of flexibility with their actual process flexibility. Originality/value This study is probably the first flexibility-measurement approach which incorporates features for capturing changes affecting the functional, operational, informational, organizational, and behavioral perspectives as well as elements related to approaches enhancing flexibility.